Facile Fabrication of Reduction-Responsive Supramolecular Nanoassemblies for Co-delivery of Doxorubicin and Sorafenib toward Hepatoma Cells - Xiong, Qingqing; Cui, Mangmang; Yu, Ge; Wang, Jian; Song, Tianqiang (Frontiers in Pharmacology, 2018)
Combination of doxorubicin with sorafenib (SF) was reported to be a promising strategy for treating hepatocellular carcinoma (HCC). In this study, we designed a reduction-responsive supramolecular nanosystem based on poly(ethylene glycol)-β-cyclodextrin (PEG-CD) and a disulfide-containing adamantine-terminated doxorubicin prodrug (AD) for efficient co-delivery of doxorubicin and sorafenib. PEG-CD/AD supramolecular amphiphiles were formed through host-guest interaction between cyclodextrin and adamantine moieties, and then self-assembled into regular spherical nanoparticles with a uniform size of 166.4 nm. Flow cytometry analysis and confocal laser scanning microscopy images showed that PEG-CD/AD nanoparticles could be successfully taken up by HepG2 cells and then released doxorubicin into the cell nuclei. Moreover, sorafenib could be facilely encapsulated into the hydrophobic cores to form PEG-CD/AD/SF nanoparticles with a slightly larger size of 186.2 nm. PEG-CD/AD/SF nanoparticles sequentially released sorafenib and doxorubicin in a reduction-response manner. In vitro cytotoxicity assay showed that PEG-CD/AD/SF had an approximately 4.7-fold decrease in the IC50 value compared to that of PEG-CD/AD and SF physical mixtures, indicating better therapeutic effect against HepG2 cells by co-loading the two drugs. In summary, this novel supramolecular nanosystem provided a simple strategy to co-deliver doxorubicin and sorafenib towards hepatoma cells, which showed promising potential for treatment of HCC.